2008
DOI: 10.1158/1078-0432.ccr-08-0258
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Levels of Reduced Folates in Patients with Colorectal Carcinoma After Infusion of Folinic Acid at Various Dose Levels

Abstract: Purpose: In patients with colorectal cancer (CRC), modulation of 5-fluorouracil (5-FU) by folinic acid (FA) improves response rate and overall survival compared with 5-FU alone. However, the optimal dose of FA is still debated.We investigated reduced folate pools in various tissues from patients with CRC without and after prior administration of FA. Experimental Design: A total of 186 specimens (normal colorectal mucosa, primary colorectal tumor, normal liver, and liver metastases) from 86 consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(20 reference statements)
3
2
0
Order By: Relevance
“…If this is the case, several patients with colorectal cancer might be receiving inadequate treatment and may benefit from leucovorin concentrations as high as 200–500 mg/m 2 . Similar conclusions were drawn by Schlemmer et al [ 15 ] in a study published in 2008, which showed significant higher values regarding reduced folates in tumour tissues as well as in liver metastasis when doses of 200 and 500 mg/m 2 were used.…”
Section: Discussionsupporting
confidence: 88%
“…If this is the case, several patients with colorectal cancer might be receiving inadequate treatment and may benefit from leucovorin concentrations as high as 200–500 mg/m 2 . Similar conclusions were drawn by Schlemmer et al [ 15 ] in a study published in 2008, which showed significant higher values regarding reduced folates in tumour tissues as well as in liver metastasis when doses of 200 and 500 mg/m 2 were used.…”
Section: Discussionsupporting
confidence: 88%
“…The results of the present study showed that there was a high inter-individual variation of folates in both tumour and mucosa. This finding is in agreement with previous results published by our group [ 18 ] as well as by others [ 23 ]. Higher concentrations were found in tumour tissue compared to mucosa in all patient groups.…”
Section: Discussionsupporting
confidence: 94%
“…This finding is in agreement with previous results published by our group [18] as well as by others [23]. Higher concentrations were found in tumour tissue compared to mucosa in all patient groups.…”
Section: Discussionsupporting
confidence: 94%
“…Administration of Modufolin ® instead of LV might circumvent such metabolic obstacles. Furthermore, an abundance of methyleneTHF in the tumor tissue may be generated by using Modufolin ® , which might lead to an increased response to 5-FU-based chemotherapy by stabilization of the ternary complex [ 11 , 25 ].…”
Section: Discussionmentioning
confidence: 99%